2004
DOI: 10.2134/agronj2004.0710
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Chicory and Plantain Cultivars under Grazing

Abstract: in 1985 and has been frequently used in the USA where good summer productivity has been reported (Jung et The bimodal distribution of growth of cool-season grass species Volesky, 1996). Chemical analyses indicate generates an imbalance in the amount of forage available during the summer, which could be improved by using alternative forage species.that Puna chicory is a high quality feed, and animal Several chicory (Cichorium intybus L.) and plantain (Plantago performance tests suggest that high liveweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
5
30
4
Order By: Relevance
“…Although that study found acceptable persistence of chicory after 3 years, and reported observations of naturalized chicory plants in the region, those results are in sharp contrast to the near complete failure of stand persistence in the present investigation. Instead, our results are more consistent with research in Pennsylvania [17] and New Zealand [18] where chicory stand losses after 1 year were as high as 50% and 33%, respectively, and up to 75% by year 4 with a 50% reduction in biomass [19].…”
Section: Forage Establishmentsupporting
confidence: 89%
See 1 more Smart Citation
“…Although that study found acceptable persistence of chicory after 3 years, and reported observations of naturalized chicory plants in the region, those results are in sharp contrast to the near complete failure of stand persistence in the present investigation. Instead, our results are more consistent with research in Pennsylvania [17] and New Zealand [18] where chicory stand losses after 1 year were as high as 50% and 33%, respectively, and up to 75% by year 4 with a 50% reduction in biomass [19].…”
Section: Forage Establishmentsupporting
confidence: 89%
“…However, our yields remained well below those from the northeastern United States, where chicory yields ranged from 6028 to 7200 kg ha -1 DM1 [28,17], and 9640 kg . ha -1 DM reported from New Zealand [19].…”
Section: Forage Yieldcontrasting
confidence: 55%
“…, Labreveux et al. ). While in Treinta y Tres, Uruguay, an area typically hotter than Palmerston North, New Zealand, Ayala et al.…”
Section: Discussionmentioning
confidence: 98%
“…In other clipped‐plot research at the same location, plant density of Puna and Forage Feast decreased by 20 to 50% during the same 2‐year period, whereas plant density of Lacerta decreased 80% (13). During 2 years of grazing management in central Pennsylvania, 25 to 45% of Puna and Forage Feast plants and 84% of Lacerta plants died (8). In New Zealand, up to 33% of Puna chicory plants died in the first year of grazing (10).…”
Section: Persistence Of Chicorymentioning
confidence: 99%